Ageing of the population in the city of Maribor - Horvat, Uroš (Journal for Geography, 2017)
In the introduction, the author analyzed the age composition of the population in larger Slovene towns and compares it with the composition in the city of Maribor. He noted that Maribor has the highest share of the older population, and the highest aging index. Further is analyzed the demographic situation in 38 local communities in the city between 1981 and 2015. It’s noted that the aging process varies in different parts of the city. In the initial period, the most unfavorable conditions were in the older part of the city on the left bank of the Drava River. During the demographic changes in the last decade, the aging of the population was more intensive in older so-called workers’ residential neighborhoods in the southern part of the town (on the right bank), where the city expanded in the 60s, 70s and 80s of the 20th century. In them a relatively age-homogeneous population was moved in at the time. On the other hand, the current situation within the older part of the city also shows favorable demographic conditions in those areas where reconstructions and revitalization occurred.